2012
DOI: 10.1016/j.pain.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species (ROS) modulate AMPA receptor phosphorylation and cell-surface localization in concert with pain-related behavior

Abstract: Sensitization of dorsal horn neurons (DHNs) in the spinal cord is dependent on pain-related synaptic plasticity and causes persistent pain. The DHN sensitization is mediated by a signal transduction pathway initiated by the activation of NMDA receptors (NMDA-Rs). Recent studies have shown that elevated levels of reactive oxygen species (ROS) and phosphorylation-dependent trafficking of GluA2 subunit of AMPA receptors (AMPA-Rs) are a part of the signaling pathway for DHN sensitization. However, the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 57 publications
8
49
0
Order By: Relevance
“…The mechanisms of insertion and deletion are beginning to be elucidated, e.g. GluA2 removal from the membrane is NMDA receptor dependent and requires phosphorylation of GluA2 at ser 880 (Beattie et al, 2000; D. Z. Lee et al, 2012; Malinow and Malenka, 2002; Park et al, 2009; Seidenman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of insertion and deletion are beginning to be elucidated, e.g. GluA2 removal from the membrane is NMDA receptor dependent and requires phosphorylation of GluA2 at ser 880 (Beattie et al, 2000; D. Z. Lee et al, 2012; Malinow and Malenka, 2002; Park et al, 2009; Seidenman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…And, oxidative stress-initiated neuroendocrine alterations within the amygdala, including amygdalar hyperactivity and dendritic shrinking (Wellman, 2001;Vyas et al, 2002;Kreibich and Blendy 2004;Brown et al, 2005;Radley et al, 2006;Wood et al, 2010), can further potentiate synaptic disturbances by disrupting the hippocampus-amygdala projections. Furthermore, free radicals are known to oxidize the extracellular sites of glutamatergic N-methyl-D-aspartate receptors, leading to attenuation of LTP and synaptic neurotransmission (Haxaire et al, 2012;Lee et al, 2012;Rai et al, 2013). Collectively, these events offer an attractive explanation for oxidative stress-induced behavioral and cognitive impairment.…”
Section: Oxidative Stress and The Brainmentioning
confidence: 99%
“…We have discussed that PpIX fluorescence positively correlates with pain experience during PDT. As the product of PpIX metabolism and effector of PDT, ROS initiate pain, especially neuropathic and capsaicin‐induced pain . ROS increase phosphorylation of N ‐methyl‐ d ‐aspartate and AMPA (α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid) receptors and decreases GABA release .…”
Section: Mechanisms Of Pain During Photodynamic Therapymentioning
confidence: 99%
“…ROS can directly activate and sensitize nociceptive neurons, and can also evoke pain indirectly by mediating release of inflammatory factors. [19][20][21][22][57][58][59] There is evidence suggesting that GABA receptors are involved in nociception during PDT. 60,61 For example, Yowtak et al showed that GABA receptors can also be inhibited by ROS.…”
Section: Pain Managementmentioning
confidence: 99%
See 1 more Smart Citation